الموازنة الصوتية وأثرها في المعنى شعر الصعاليك نموذجا - منال، با, جهاد، بالعايش; فضيلة الزين، سايح (Univesity of El-Oued, 2022)
من خلال درستنا للموازنة الصوتية وأثرها في شعر الصعاليك توصلنا لعدة استنتاجات وهي كالأتي : 1. أن معنى الصعلكة هو الفقر، أما الصعاليك فهم جماعة احترفوا القتال والغزو وحمل السلاح، وكان هدفهم إغناء الفقراء وإعانة الأرامل. 2. أن مفهوم الموازنة الصوتية عند ابن رشيق ينحصر في المقابلة والتجنيس والترصيع، أما عند محمد العمري فيتجسد في الموافقة والمخالفة والتجنيس والترصيع. 3. اختلف اللغويون العرب من قدماء ومحدثين في تحديد مفهوم الصوت والمعنى كل حسب رؤيته ومنهجه 4. وظف الشعراء الصعاليك الموازنة الصوتية في قصائدهم مع تفاوت في استعمالها كل حسب ظروف معيشته. Through our study of the acoustic balance and its impact on the poetry of the rebels, we reached several conclusions, which are as follows: 1. We concluded that the meaning of rebellion is poverty. As for the rebels, they are a group that has specialized in fighting, conquest and carrying arms, and their goal was to enrich the poor and support widows. 2. The concept of phonetic balancing according to Ibn Rashiq is limited to opposites and alliteration, and inlaying, while according to Muhammad al-Omari it is embodied in agreement, dissent, alliteration and inlay. 3. Arab linguists, both ancient and modern, differed in defining the concept of sound and meaning, each according to his vision and approach. 4. The rebel poets employed the phonetic balance in their poems, with varying uses, each according to his living conditions.
Keywords: الصعلكة، الموازنة الصوتية، المنهج الصوتي، دلالة الأصوات; rebellion, vocal balancing, phonemic method, sound indication.